Endoscopic treatment of hepaticojejunostomy anastomotic strictures using fully‐covered metal stents. Issue 3 (28th August 2020) - Sato, Tatsuya; Kogure, Hirofumi; Nakai, Yousuke; Kanai, Sachiko; Ishigaki, Kazunaga; Hakuta, Ryunosuke; Saito, Kei; Saito, Tomotaka; Takahara, Naminatsu; Hamada, Tsuyoshi; Mizuno, Suguru; Yamada, Atsuo; et al.
Abstract : Objectives: With the emergence of the double‐balloon endoscope (DBE), hepaticojejunostomy anastomotic strictures (HJASs) are increasingly managed endoscopically. However, balloon dilation and/or plastic stent placement may be associated with low stricture resolution rates and long treatment duration. We utilized a fully‐covered metal stent (FCSEMS), which was designed for temporary placement for benign biliary strictures, and assessed its feasibility for patients with HJASs. Methods: We retrospectively studied 20 patients who underwent DBE‐assisted FCSEMS placement for HJASs between June 2017 and March 2019. The FCSEMS was removed endoscopically at three months of stent placement. The outcomes investigated were the stricture resolution at the time of FCSEMS removal, the stricture recurrence, and adverse events. Results: Among 20 patients treated, stricture resolution was achieved in 17 patients (85.0%) at three months of stent placement. The FCSEMS was removed endoscopically without any technical difficulties in all cases except for two with asymptomatic stent migration due to stricture resolution. During a median follow‐up period of 11.9 months (interquartile range, 7.5–18.0 months), an HJAS recurred in one patient (5.9%). For two patients without stricture resolution and one patient with recurrent stricture, another FCSEMS placement for 77, 84, and 186 days resolved the stricture. The overall stricture resolution rate was 95.0%. In one patient with FCSEMS‐induced de novo stricture, long‐term plastic stent placement was required. Procedure‐related adverse events included mild cholangitis in two patients and mild pancreatitis in one patient. Conclusions: Endoscopic treatment using a FCSEMS via DB‐ERCP was a feasible and effective treatment option for a HJAS.